Letter (copy) : German activities in the Basque Country - Tewson, Vincent
012b-0060-001 Secretary's. HVT/FC/EK/658. 30th January, 1939. Signor J. I. de Lizaso, 14, Eccleston Square, London, S.W.1. Dear Sir, GERMAN ACTIVITIES IN THE BASQUE COUNTRY. Your letter of the 28th instant addressed to Sir Walter has been received and the contents carefully noted. I should be glad if you would let me know whether this information has been conveyed to the British Government in any way. If it has not I will see that they are acquainted with the reports which you have received. I should be pleased to receive a reply on this matter as early as possible. Yours faithfully, Assistant Secretary, 292/946/12b/60